2005
DOI: 10.1109/jcn.2005.6387987
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of space-time codes in realistic propagation environments: A moment generating function-based approach

Abstract: Abstract-UWB pulses are the unique labels of UWB systems. This paper investigates the role of pulse systematically and highlights the central position of the pulse in UWB systems. Four system properties related closely to the pulse are discussed: propagation properties, capacity, interference to existing systems and performance of correlation receivers. The properties of pulses which function directly on every aspect are highlighted. Novel viewpoint is provided for the evaluation of capacity and interference. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In [13], it was shown that the correlation between the n-th and n -th modes at the 5 The exact-PEP expression we derived in this work can be applied to any arbitrary antenna configuration. 6 Second order statistics of the scattering channel H S .…”
Section: Effect Of Modal Correlationmentioning
confidence: 95%
See 2 more Smart Citations
“…In [13], it was shown that the correlation between the n-th and n -th modes at the 5 The exact-PEP expression we derived in this work can be applied to any arbitrary antenna configuration. 6 Second order statistics of the scattering channel H S .…”
Section: Effect Of Modal Correlationmentioning
confidence: 95%
“…Using the partial fraction expansion technique given in [13] and a result found in [17], the integral in (28) can be evaluated in closed form.…”
Section: B Exact-pep For Correlated Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming the power distribution at the receiver is independent of the power distribution at the transmitter, the correlation matrix of the channel (2) can be written as [12] where y(k) = (vec{Y(k)T})T, X(k) = R X (FX(k)), h = (vec{HT})T, n(k) = (vec{N(k)T})T, Sf(k) = InpR S(k) and w(k) = n(k)-n(k-1)S(k). From (5), the transmitted code word matrix can be detected differentially using the maximum likelihood detection rule: Sf(k) = arg max Re{y(k -)Sf(k)y(k)t}.…”
Section: Introductionmentioning
confidence: 99%
“…Such an assumption is valid only if the scattering environment is isotropic, i.e., scattering is uniformly distributed over the receiver and transmitter antenna arrays, and also only if the antennas in an array are well separated. Recent studies have shown that insufficient antenna spacing and non-isotropic scattering reduce the performance of space-time coded communication systems [9][10][11]. This has motivated the design of linear precoders for space-time coded multiple antenna systems by exploiting the statistical information of the MIMO channels [12][13][14][15][16][17].…”
mentioning
confidence: 99%